2011
DOI: 10.1186/1471-2180-11-98
|View full text |Cite
|
Sign up to set email alerts
|

Fusidic acid resistance among clinical isolates of methicillin-resistant Staphylococcus aureus in a Taiwanese hospital

Abstract: BackgroundThe prevalence of resistance to fusidic acid of methicillin-resistant Staphylococcus aureus (MRSA) was increased each year in a Taiwan hospital. Thirty-four MRSA clinical isolates collected in 2007 and 2008 with reduced susceptibility to FA were selected for further evaluation the presence of resistance determinants.ResultsThe most common resistance determinant was fusC, found in 25 of the 34 MRSA isolates. One of the 25 fusidic acid-resistant MRSA harboured both fusB and fusC, which is the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 31 publications
(57 reference statements)
0
37
2
5
Order By: Relevance
“…Isolates that exhibited phenotypic resistance to particular antimicrobial agents for which associated resistance genes were not detected by the DNA microarray, or for which resistance genes were detected but partial or none of the associated resistance phenotypes were detected, were further investigated by PCR to confirm the presence or absence of these resistance genes. These investigations included PCRs using previously described primers to detect mupA (36), aphA3 (37), aacA-aphD (37), fusB (38), tet(K) (36), tet(M) (36), aadD (39), and qacA (40), and also novel primers to detect qacC, msr(A), dfrS1, lnu(A), mph(C), and blaZ (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Isolates that exhibited phenotypic resistance to particular antimicrobial agents for which associated resistance genes were not detected by the DNA microarray, or for which resistance genes were detected but partial or none of the associated resistance phenotypes were detected, were further investigated by PCR to confirm the presence or absence of these resistance genes. These investigations included PCRs using previously described primers to detect mupA (36), aphA3 (37), aacA-aphD (37), fusB (38), tet(K) (36), tet(M) (36), aadD (39), and qacA (40), and also novel primers to detect qacC, msr(A), dfrS1, lnu(A), mph(C), and blaZ (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Our results indicated that 19 (41%) isolates had fusA mutations and 27 (59%) carried the fusC gene (Table 1). Compared to the occurrence of fusC in our previous report, the prevalence of fusC has increased among the fusidic acid-resistant MRSA isolates (4,5).…”
mentioning
confidence: 99%
“…We previously identified the fusidic acid resistance determinants in 45 methicillin-resistant S. aureus (MRSA) and 26 methicillin-susceptible S. aureus (MSSA) isolates collected from 2002 to 2007 and found that the fusA mutation was the major determinant responsible for resistance in MRSA (4). However, another group in central Taiwan found that fusC was the predominant determinant (5). To obtain more-up-to-date information about the prevalence of resistance determinants in MRSA, we examined the 46 fusidic acid-resistant (MIC, Ն2 g/ml) isolates of MRSA collected during a 3-year period (2008 to 2010) by the Bacteriology Laboratory, National Taiwan University Hospital.…”
mentioning
confidence: 99%
“…Fusidik asit direnç genlerinin prevalansında coğra-fik farklılıklar bulunduğu bildirilmiştir. [15][16][17] Fusidik asit Amerika Birleşik Devletleri'nde lisanslı olmadığından, CLSI'nın in vitro duyarlılık değerleri için herhangi bir önerisi bulunmamaktadır. Ancak gerek İngiliz Antimikrobiyal Kemoterapi Derneği, gerek Fransa Mikrobiyoloji Derneği, gerekse bu konuda standart oluşturmak için yapılan çalışmalar, fusidik asidin stafilokoklar için MİK değerlerini duyarlı, orta duyarlı ve dirençli olmak üzere sırasıyla; ≤0,125 mg/L, 0,5-1 mg/L ve ≥2 mg/L olarak bildirmektedir.…”
Section: Discussionunclassified